(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Creativity is the capacity to produce new ideas that leads to inventions and innovations when put in to practice. Progress of a nation in all walks of life depends upon creative people. The persons who think originally are known as creative person and this quality is known as creativity. This era of science is converted into the era of creative science, studies are known as advanced studies, literature also is advanced now. Every sphere of life is filled with creative work. Scientists, artists, poets, musicians all are creative genius. People have been born with equal intelligence but environment guidance and facilities make differences among people. The idea of individual difference is caused by the unequal environmental conditions, which is created by the education system.